2011
DOI: 10.1186/1471-2318-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Designing clinical trials for assessing the effects of cognitive training and physical activity interventions on cognitive outcomes: The Seniors Health and Activity Research Program Pilot (SHARP-P) Study, a randomized controlled trial

Abstract: BackgroundThe efficacy of non-pharmacological intervention approaches such as physical activity, strength, and cognitive training for improving brain health has not been established. Before definitive trials are mounted, important design questions on participation/adherence, training and interventions effects must be answered to more fully inform a full-scale trial.MethodsSHARP-P was a single-blinded randomized controlled pilot trial of a 4-month physical activity training intervention (PA) and/or cognitive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
4
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 49 publications
4
125
4
7
Order By: Relevance
“…The CFA displayed good fit indices despite the small sample size, disregarding TS. Previous studies have generally had fewer tasks and/or investigated fewer constructs (Burns et al, 2009; Erickson et al, 2011; Legault et al, 2011; Thomas et al, 2016). Thus, the present observation that aerobic exercise compared to stretching and toning control training was more effective in improving cognition in older adults is an important contribution to a field showing equivocal results, owing at least in part, to a lack of robust test batteries enabling use of latent constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFA displayed good fit indices despite the small sample size, disregarding TS. Previous studies have generally had fewer tasks and/or investigated fewer constructs (Burns et al, 2009; Erickson et al, 2011; Legault et al, 2011; Thomas et al, 2016). Thus, the present observation that aerobic exercise compared to stretching and toning control training was more effective in improving cognition in older adults is an important contribution to a field showing equivocal results, owing at least in part, to a lack of robust test batteries enabling use of latent constructs.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, numerous investigations have addressed the relationships between physical exercise and cognition (e.g., Khatri et al, 2001; Fabre et al, 2002; Legault et al, 2011; Langlois et al, 2013). Despite the wealth of literature showing how staying physically active may prevent cognitive decline (Yaffe et al, 2001; Sofi et al, 2011), dementia onset (Laurin et al, 2001; Yaffe et al, 2009), and improve brain-behavior relationship throughout the lifespan (Boraxbekk et al, 2016), there are also studies, e.g., a recent Cochrane review (Young et al, 2015), that have concluded that aerobic exercise, compared to active control training, had no added benefit on any cognitive function investigated.…”
Section: Introductionmentioning
confidence: 99%
“…7 Two recent small RCTs of physical activity found no benefit of a structured physical activity program vs. no intervention or cognitive training in non-demented older adults with cognitive complaints or at risk of cognitive decline. 10;11 However, a 6-month RCT of a home-based physical activity program vs. usual care in participants with memory complaints or mild cognitive impairment found a modest cognitive benefit. 12 The LIFE Pilot study showed a correlation between changes in physical and cognitive performance in a 12 month exercise trial.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study involving comparison of cognitive training and physical activity or a combination of both, the researchers screened 343 potential subjects in order to enroll just 73 participants, a 21% enrollment rate [20]. Most were excluded as they were ineligible after further screening related to study exclusion criteria, but it appears a portion were also merely unwilling to participate in the research program.…”
Section: Introductionmentioning
confidence: 99%